Possible explanation for the tail of the cosmic ray spectrum - Anchordoqui, Luis Alfredo (2000)
A re-examination of the energy cosmic ray spectrum above 1020 eV is presented. The overall data-base provides evidence, albeit still statistically limited, that non-nucleon primaries could be present at the end of the spectrum. In particular, the possible appearance of superheavy nuclei seldom discussed in the literature is analysed in detail.